Aggregation induced emission enhancement by plasmon coupling of noble metal nanoparticles. (18th September 2019) - He, Jiangling; Li, Shuang; Lyu, Da; Zhang, Dingfeng; Wu, Xiao; Xu, Qing-Hua
Abstract : Aggregation induced plasmon coupling enhanced fluorescence of a pre-quenched chromophore has been demonstrated by using Au and Au@Ag nanoparticles, which could be further utilized to develop highly sensitive chemical and biological sensing schemes. Abstract : Materials that display aggregation induced emission (AIE) can offer large contrast ratio for highly sensitive fluorescence based applications such as sensing and imaging. Conventional AIE chromophores are generally based on improved emission quantum yield due to reduced nonradiative decay rates by restriction of intramolecular motion. In this work we present another type of AIE phenomenon with a totally different working mechanism. It is based on aggregation induced plasmon coupling of metal nanoparticles (NPs) to simultaneously enhance the excitation efficiency and radiative decay rate of chromophores. The unique surface plasmon resonance (SPR) properties of noble metal NPs can give rise to a significantly enhanced local electric field to modulate the optical properties of nearby chromophores. Plasmon coupling interactions between adjacent metal NPs can cause giant enhancement in the local electric field and consequently even stronger enhancing capability. The working principle was demonstrated by using rhodamine B isothiocyanate (RiTC) as the model chromophore and cysteine as the coupling agent to induce aggregation of noble metal NPs. The fluorescence of RiTC was pre-quenched by attaching to the surface of Au and core–shell Au@Ag NPs. Upon addition of cysteine to induce the aggregation of RiTC conjugated Au@Ag NPs, the fluorescence of RiTC was significantly enhanced to a level much beyond that of fluorescence recovery. A series of core–shell Au@Ag NPs with different Ag shell thicknesses have been prepared to optimize the performance of aggregation induced plasmon coupling enhanced fluorescence. The optimum enhancement effect was achieved for Au@Ag NPs with a 5.6 nm Ag shell, which enhanced the fluorescence intensity of RiTC in the coupled nanostructures to be 44.8 times stronger than that of pre-quenched RiTC and 7.6 times that of free RiTC. Based on this method, the limit of detection of 3.4 pM was obtained for the detection of cysteine, which is highly selective and more sensitive than most previously reported methods. This quenched-enhanced (off–on) method is highly sensitive, simple, straightforward and universal, and can be easily extended for the detection of other analytes.